Peptides obtained from proteins of cobia (Rachycentron canadum): a study of potentially safe antioxidants for food - Dos Santos Da Fonseca, Renata Aline (2017)
The fish and its by-products from industrial processing are a rich source of protein. For this reason, cobia (Rachycentron canadum), a large and easily adaptable to aquaculture species has emerged as an option for obtaining peptides. Enzymatic proteolysis is able to release inactive biopeptides ? which may have greater activity when separated into their peptide fractions ? from intact proteins. However, as they can be applied in food, they should be evaluated for any possible harm to health. Thus, this study aimed to evaluate the ability of the protein hydrolysates of cobia (muscle and waste), obtained by the action of Alcalase, Flavourzyme and Protamex enzymes (whole and their fractions less and major than 3 kDa) to inhibit the oxidation of meat food and ensure their food security. The hydrolysates studied in this work demonstrated antioxidant activity through chemical methods in vitro. All hydrolysates and their fractions were not cytotoxic to zebrafish (Danio rerio) hepatocytes at the concentrations of 0.1, 1.0, 10 and 100 g/mL at 0, 24, 48 and 72 h. By etermining the 25 inhibition of thiobarbituric acid reactive substances in bacon and ground beef it was found that the majority of the hydrolysates presented this capacity, highlighting the peptide fractions major than 3 kDa of muscle hydrolysates which reduced by around 50% the TBARS (thiobarbituric acid reactive substances) content formed in the ground beef, and by more than 80% in bacon, probably because the bacon has a higher content of lipid. The enzyme Protamex provided hydrolyzed with more antioxidant activity. Therefore, these results indicate that the hydrolysates studied have the potential to be safe physicochemically, not cytotoxic, used in foods as antioxidants.